Comparative Analysis of Charlie Chaplin Animations: Safari at The Park and The King in The Ring Using Peirce’s Triadic Theory - Nadia Kumari; Melyana Pinem; Riscitta Ogilvie Hubertus Sinaga; Jessica Hotnida Nainggolan; Meisuri Meisuri (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study analyzes visual signs in the Charlie Chaplin animations Safari at The Park and The King in The Ring using Charles Sanders Peirce’s semiotic framework, focusing on icons, indexes, and symbols. Film and animation communicate meaning through visual elements such as gestures, facial expressions, movements, and character interactions, making them rich for semiotic analysis. Using a descriptive qualitative method, the research identified and categorized visual signs in both animations. Results show that icons, which resemble real-world objects, dominate by establishing story settings natural safari environments in one animation and competitive boxing arenas in the other. Indexes reveal cause-and-effect relationships, demonstrating how gestures, expressions, and actions convey danger, fatigue, or emotional shifts. Symbols convey conventional or cultural meanings, such as Charlie Chaplin’s bowler hat and cane representing his comedic identity, a championship belt symbolizing victory, or a rose indicating affection. While both animations use the same types of signs, the intensity and focus vary with the narrative context: Safari at The Park emphasizes situational and natural elements, whereas The King in The Ring highlights competition and emotional reactions. This study confirms that Peirce’s triadic model effectively explains how meaning is constructed in animation through dynamic visual communication.